The influence of parenting, self-efficacy, and entrepreneurial interest toward the learning motivation of creative products and entrepreneurship of culinary management vocational school students - Naning Yulianti Antonia; Badraningsih Lastariwati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aims to reveal the effects of (1) parenting, (2) self-efficacy, (3) entrepreneurial interest, and (4) parenting, self-efficacy, and interest in entrepreneurship simultaneously on the motivation to learn creative products and entrepreneurship in class XII vocational school of Catering Services Department in Magelang. This research is ex-post facto research. The research population was 201 students of the Catering Services Department from two vocational schools in Magelang. The sample consisted of 127 students who were taken using the proportional random sampling technique. The data analysis technique used descriptive analysis and regression analysis. The results showed that: Parenting, self-efficacy, and interest in entrepreneurship were able to predict learning motivation with an effective contribution to parenting (5.15%, high category); self-efficacy (3.63, low category); interest in entrepreneurship (32.80%, very high category). The coefficient of determination (R2) is 0.416 (41.6%), which means that 41.6% of students' motivation to learn creative products and entrepreneurship in class XII of the Catering Services Department are influenced by parenting, self-efficacy, and interest in entrepreneurship, while the remaining 58.4% is influenced by other variables that are not examined in this study.